Effectiveness of Interactive Multimedia Web-Based Tutorial Model to Improve Pedagogical Competence of Elementary School Teachers in Karangpawitan District, Garut Regency - Elin Purnamasari; Nizar Alam Hamdani; Iman Nasrulloh (Riviera Publishing, 2026)
This study aims to analyze the effectiveness of interactive multimedia web-based tutorial models in improving teachers' pedagogical competence in Karangpawitan District. The research problem stems from the still low pedagogical competence of teachers in lesson planning, utilization of digital media, authentic assessment, and technology-based learning management. The study used a quantitative approach with a quasi-experimental method through a pretest-posttest control group design. The research sample consisted of 60 elementary school teachers divided into experimental and control groups. Data collection techniques used tests, questionnaires, observation, and documentation. Data analysis used descriptive statistics, normality tests, homogeneity tests, and t-tests. The results showed that interactive multimedia web-based tutorial models were effective in improving teachers' pedagogical competence. The average score of the experimental group increased from 62.15 to 85.40, while the control group increased from 61.80 to 70.25. The t-test results showed a significance value of 0.000 <0.05. Thus, interactive multimedia web-based tutorial model has proven effective in improving the pedagogical competence of teachers in Karangpawitan District, Garut Regency.